Objetivos de Desarrollo Sustentable y funciones sustantivas en las Instituciones de Educación Superior - García-Arce, Julia Guadalupe; Pérez- Ramírez, Carlos Alberto; Gutiérrez Barba, Blanca Estela (Universidad de Costa Rica, 2021)
The Sustainable Development Goals (SDGs) establish a framework to be able to fulfil the purposes of sustainability in its multiple social, economic, and environmental dimensions. While the Higher Education Institutions (HEIs), can be considered as a determinant social actor to support their fulfilment. The aim of this article proposes a compilation of criteria for the analysis of the SDGs based on four main functions of university activity: institutional management, environmental and culture university practices; education and learning; research; and social leadership. For this a literature review was conducted during the period January to June 2020, in which the outputs were eight analytical and reference frameworks of various institutions at the international level and in Mexico has been carried out, which resulted in the coincidence of 32 criteria classified according to the main functions of the HEIs; which allowed the elaboration of word clouds to determine the key elements for indicators, thus also allowing for an understanding of the achievements and limitations of the HEIs for the fulfilment of the SDGs and the promotion of sustainability. Preliminarily, although there is no in situ verification, it can be concluded that HEIs can facilitate the SDGs and the environmental dimension of sustainability through their substantive functions.